Bevacizumab Treatment of Radiation-Induced Brain Necrosis: A Systematic Review - Liao, Guixiang; Khan, Muhammad; Zhao, Zhihong; Arooj, Sumbal; Yan, Maosheng; Li, Xianming (Frontiers in Oncology, 2021)
Background: Radiation brain necrosis (RBN) is a serious complication in patients receiving radiotherapy for intracranial disease. Many studies have investigated the efficacy and safety of bevacizumab in patients with RBN. Materials and Methods: We searched PubMed, Cochrane library, EMBASE, and ClinicalTrials.gov from their inception through 1 March, 2020 for studies that evaluated the efficacy and safety of bevacizumab in patients with RBN. Two investigators independently performed the study selection, data extraction, and data synthesis. Results: Overall, the present systematic review included 12 studies (eight retrospective, two prospective, and two randomized control trials [RCTs]) involving 236 patients with RBN treated who were treated with bevacizumab. The two RCTs also had control arms comprising patients with RBN who were treated with corticosteroids/placebo (n=57). Radiographic responses were recorded in 84.7% (200/236) of patients, and radiographic progression was observed in 15.3% (36/236). Clinical improvement was observed in 91% (n=127) of responding patients among seven studies (n=113). All 12 studies reported volume reduction on T1 gadolinium enhancement MRI (median: 50%, range: 26%–80%) and/or T2 FLAIR MRI images (median: 59%, range: 48%–74%). In total, 46 responding patients (34%) had recurrence. The two RCTs revealed significantly improved radiographic response in patients treated with bevacizumab (Levin et al.: p = 0.0013; Xu et al.: p < 0.001). Both also showed clinical improvement (Levin et al.: NA; Xu et al.: p = 0.039) and significant reduction in edema volume on both T1 gadolinium enhancement MRI (Levin et al.: p=0.0058; Xu et al.: p=0.027) and T2 FLAIR MRI (Levin et al.: p=0.0149; Xu et al.: p < 0.001). Neurocognitive improvement was significantly better after 2 months of treatment in patients receiving bevacizumab than in those given corticosteroids, as assessed by the MoCA scale (p = 0.028). The recurrence rate and side effects of the treatments showed no significant differences. Conclusions: Patients with RBN respond to bevacizumab, which can improve clinical outcomes and cognitive function. Bevacizumab appears to be more efficacious than corticosteroid-based treatment. The safety profile was comparable to that of the corticosteroids.